2017
DOI: 10.7759/cureus.955
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Traumatic Giant Macular Hole Repair with Autologous Platelets

Abstract: We report on the closure of a chronic posttraumatic giant macular hole. The patient presented with decreased vision in the left eye following blunt trauma 20 years prior. His dilated fundus examination revealed a 3000 um base-diameter full thickness macular hole. Surgical repair was performed with pars plana vitrectomy (PPV), internal limiting membrane peeling and autologous platelet concentrate (APC) injected over the macular hole. At one month follow-up, the macular hole had closed on exam and optical cohere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…4 A prior report of the use of APC was reported by Wachtlin et al in four pediatric patients with macular hole though these holes were around 300 μm in size. 15,16 Our technique combined these two methods: we believe this technique is particularly advantageous for pediatric patients with a large macular hole as the APC with the ILM flap provide a strong plug and a scaffold for cell proliferation to seal the hole and allow for anatomical closure. Intraoperative OCT was particularly helpful in this case in confirmation of the location of the ILM flap as well as the placement of the APC.…”
Section: Discussionmentioning
confidence: 99%
“…4 A prior report of the use of APC was reported by Wachtlin et al in four pediatric patients with macular hole though these holes were around 300 μm in size. 15,16 Our technique combined these two methods: we believe this technique is particularly advantageous for pediatric patients with a large macular hole as the APC with the ILM flap provide a strong plug and a scaffold for cell proliferation to seal the hole and allow for anatomical closure. Intraoperative OCT was particularly helpful in this case in confirmation of the location of the ILM flap as well as the placement of the APC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, vitrectomy with membrane peeling might be helpful and is a standard surgical procedure for treating TMH ( 6 ). Currently, PPV, ILM peeling or flap, and intraocular gas or silicone oil tamponade are the most commonly employed surgical procedures for TMH treatment ( 5 ). Ghoraba et al concluded that gas tamponade is more successful than silicone oil tamponade for the anatomical closure and VA improvement of TMH ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, surgical techniques include removing the posterior vitreous cortex and epiretinal membranes, with or without internal limiting membrane (ILM) peeling, and intraocular gas or silicone oil tamponade. Various adjuvant therapies, including transforming growth factor-beta (TGF-β), biological tissue adhesives, and platelet concentrate, have been investigated with varying degrees of success ( 5 , 6 ). However, there are many unanswered questions about the necessity of surgery because spontaneous hole closure has been commonly reported ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 33 ] Coca et al .reported successful anatomical closure of a single chronic traumatic MH with BD of 3000 μm. [ 34 ] However, most of the reports are either single-arm non-comparative studies or include small MHs. The efficiency of platelets for large macula holes is limited to mere case reports.…”
Section: Discussionmentioning
confidence: 99%